The impact of Covid-19 on electronic payment system: Lesson learned from Indonesian banking - Farida, Farida; Binastuti, Sugiharti; Silfianti, Widya; Hermana, Budi (Technium Social Sciences Journal, 2023)
The Indonesian economy suffered a recession due to the COVID-19 pandemic, the first case of which was announced on March 3, 2020. In response to this disaster, various economic sectors carried out digital transformation, including the banking sector. This research is a case study of how Indonesian banking responded to the pandemic through various central bank policies complemented by literature review on the impact of the pandemic on the banking sector in the world, as well as the development of electronic payment systems before, during and after the COVID-19 pandemic. The central bank issued several regulations of relaxation to reduce the impact of the pandemic on the banking sector. From the perspective of society, the pandemic has actually accelerated the use of digital payment systems in Indonesia. The most widely used electronic payment instrument is electronic money, followed by RTGS transactions with data periods ranging from 2016 to 2021. ATM/Debit card transactions show relatively no fluctuating increases, while credit card transactions show a decline during the same observation period. The trend of increasing electronic transactions is expected to continue after the pandemic and will become a necessity in the Indonesian economy onwards